Hubungan Literasi Kesehatan Orangtua Remaja Putri terhadap Sikap dan Self-Efficacy Terkait Vaksinasi Human Papillomavirus - Dora Samaria; Nevin Zhasmin Mizka (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Adolescents typically lack complete autonomy in making medical decisions, with parental influence often playing a pivotal role in matters such as consenting to or declining medical interventions, including human papillomavirus (HPV) vaccination for their daughters. However, scholarly investigation into parental health literacy concerning attitudes and self-efficacy regarding HPV vaccination for adolescent girls remains limited. This study aims to ascertain the correlation between parental health literacy levels and their attitudes towards, as well as self-efficacy regarding, HPV vaccination. This cross-sectional inquiry was carried out between February and June 2023, involving 197 parents of teenage daughters. Utilizing consecutive sampling techniques, participants were recruited from the UPTD catchment area of Pejuang Health Center, Bekasi. Research instruments employed encompassed the Health Literacy questionnaire, the Attitude Questionnaire concerning the HPV vaccine, and the Self-Efficacy Scale for HPV vaccination. Data analysis entailed the application of the Spearman Correlation Test. Predominantly, respondents were female, aged between 31 and 40 years, married, with one teenage daughter, and predominantly relied on electronic media for health literacy information. Significantly positive associations were established between parental health literacy and attitudes (p value=0.000; r=0.339), as well as self-efficacy (p value=0.000; r=0.301). Parental health literacy exhibits a substantial correlation with attitudes and self-efficacy regarding HPV vaccination, characterized by a moderate strength of association. Consequently, an intervention initiative targeting the enhancement of parental health literacy is advocated, the efficacy of which could be evaluated through prospective quasi-experimental research endeavors. Keywords: Parental Health Literacy, Attitude, Self-Efficacy, Adolescent Women, Human Papillomavirus Vaccination.  ABSTRAK Remaja putri belum memiliki independensi penuh untuk mengambil keputusan medis. Peran orangtua sangat berpengaruh terhadap tindakan medis untuk anak mereka, temasuk untuk menyetujui atau menolak vaksinasi human papillomavirus (HPV). Penelitian terkait literasi kesehatan orang tua yang berkaitan dengan sikap dan efikasi diri dalam vaksinasi HPV bagi remaja putri masih terbatas. Mengindentifikasi hubungan antara literasi kesehatan orangtua dengan sikap dan self-efficacy terkait vaksinasi HPV. Studi potong lintang ini dilakukan pada bulan Februari-Juni 2023 pada 197 orangtua yang memiliki remaja putri. Sampel diseleksi menggunakan teknik consecutive sampling di wilayah kerja UPTD Puskesmas Pejuang, Bekasi. Instrumen penelitian meliputi, Helath Literacy questionnaire, Kuesioner Sikap terkait vaksin HPV dan, Self-Efficacy Scale for the HPV vaccination questionnaire. Data yang terkumpul diolah menggunakan Uji Korelasi Spearman. Mayoritas responden berjenis kelamin perempuan, berusia 31-40 tahun, berstatus menikah, memiliki 1 remaja putri, dan mengandalkan media elektronik sebagai sumber literasi kesehatan mereka. Ditemukan hubungan yang signifikan antara literasi kesehatan orang tua dengan sikap (p value=0,000; r=0,339) dan self-efficacy (p value=0,000; r=0,301). Literasi kesehatan orangtua memiliki hubungan yang bermakna dengan sikap dan self-efficacy terkait vaksinasi HPV, dengan kekuatan hubungan yang moderat. Direkomendasikan program intervensi untuk meningkatkan literasi kesehatan orangtua yang dapat dievaluasi efektivitasnya melalui penelitian kuasi eksperimental di masa mendatang.   Kata Kunci: Literasi Kesehatan Orangtua, Sikap, Self-Efficacy, Remaja Putri, Vaksinasi Human Papillomavirus.